Peningkatan Kualitas Produk Abon Bandeng Babon Senyum dengan Metode Kano dan QFD - Muhammad Echang Komarudin; Yanuar Pandu Negoro; Hidayat Hidayat (Jurnal Optimalisasi, 2023)
In the era of rapid development of the culinary industry, companies of all sizes must compete to improve the quality of their products in order to remain relevant in the current era of free trade, Quality product design refers to the design of products that not only fulfill their basic functions, but also in accordance with quality, capacity, and appearance that satisfies customers. The company is aware of the importance of improving as well as developing the best products. Therefore, how a business wants to identify the needs and wants of consumers. This study applies QFD and Kano methods. Data collection methods in this study are conservation, interviews and distributing questionnaires. To understand the characteristics of shredded milkfish products, smile baboons that are in accordance with consumer desires, using Kano and continued with QFD analysis and then included in the House of quality, aimed at prioritizing development. The purpose of this study is to bring out what are the attributes of baboon shredded milkfish products that are expected to lift product quality. The results of this study show that there are 20 attributes that are expected by consumers and 14 technical responses, the main things of development include making new packaging, sorting and inspecting raw materials, choosing writing or fonts that are easy to read by buyers or enthusiasts, also the most important is to promote through Instagram to boost the popularity of products from smile baboons.